The Influence of Company Size, Tax Planning, and Corporate Social Responsibility on Earning Management in Indonesia - Ekaputra, Mohamad Yandy; Meini, Zumratul (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
This study examines the effect of company size, tax planning, and corporate social responsibility on earnings management in basic material manufacturing companies on the Indonesia Stock Exchange during the period 2018-2022. Using purposive sampling, this study involved 26 companies. The data used are secondary data from the company's financial statements. The analysis was carried out using multiple linear regression. The results show that company size and tax planning have a negative effect on earnings management, while corporate social responsibility has no effect on earnings management. This indicates that larger companies and those with more effective tax planning tend to reduce earnings management practices, whereas corporate social responsibility is not directly related to earnings management.